IMPLEMENTASI SINGLE PRESENCE POLICY (SPP) BAGI DUNIA PERBANKAN DALAM PERSPEKTIF UNDANG UNDANG NOMOR TAHUN 2007 TENTANG PERSEROAN TERBATAS - Pujiyono, Pujiyono (Yustisia, 2012)
AbstractThe objectives of this research are to know the implementation of Single Presence Policy for Banking in the Law number 40th of 2007 about Limited Company (The Law of Limited Company)  perspective and to know the supporting and resisting factors in  implementation of Single Presence Policy for Banking in The Law of Limited Company perspective. The datas consist of primary and secondary data. The primary data is collected by interview. The secondary data is collected by documentary research. Bank Indonesia region of Surakarta is chosen because its rule as  supervisor and builder public bank  asspecially at Surakarta region. The result of this research shows that the implementation of single presence policy is causing : inquietable at state banking with tree options are offered by government, labour problems and the problem about legal owner and beneciary owner. The supporting  factor in the implementation of Single Presence Policy for world banking in The Law of Limited Company perspective  are : It as media to increase the competitive ratio of Government Bank and it as a tool to gives limitation the domination of private bank by foreign owner. The resisting factors in  implementation of Single Presence Policy for world banking in The Law of Limited Company perspective  are : The law problems, the collision of the Single Presence Policy and the RUPS system in The Law of Limited Company about Single Presence Policy, The accomplishment of minimum core capital, The insiding of PBI no  8/16/PBI/2006 about Single Ownership of Indonesian Banking to Minority Shareholders, and the difficult of applying holding company at Government bank.